The Enigma of Ethiopia's Hairy Kings - Ramos, M. (Lectures of The Anglo-Ethiopian Society. SOAS University of London, 21 February, 2019)
The study of Northern Ethiopian cultural traditions has historically been devalued, but they are a rich and extremely varied counterpoint to written accounts. This lecture will highlight the advantages of confronting oral legends with written, iconographic and architectural testimonies to better grasp the political and religious crises that affected the Ethiopian kingdom in the first half of the 17th century.